Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/ijms23073817
|View full text |Cite
|
Sign up to set email alerts
|

Recent and Ongoing Research into Metastatic Osteosarcoma Treatments

Abstract: The survival rate for metastatic osteosarcoma has not improved for several decades, since the introduction and refinement of chemotherapy as a treatment in addition to surgery. Over two thirds of metastatic osteosarcoma patients, many of whom are children or adolescents, fail to exhibit durable responses and succumb to their disease. Concerted efforts have been made to increase survival rates through identification of candidate therapies via animal studies and early phase trials of novel treatments, but unfort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 187 publications
0
48
0
Order By: Relevance
“…Stimulation of the immune system can also be achieved by synthetic molecules, such as mifamurtide (immune modulator liposomal muramyl tripeptide), which is a synthetic derivative of a peptidoglycan that makes up the plasma membrane of bacillus Calmette–Guerin. In cancer, mifamurtide induces the activation of monocytes and macrophages against tumors via the secretion of IL-6, TNFα and increased anti-tumor activity of infiltrating immune cells [ 166 ]. The addition of mifamurtide showed an increase in event-free life span and overall survival [ 167 , 168 ] but without a significant difference between non metastatic and metastatic patients [ 169 ].…”
Section: New Therapeutic Approaches In Osmentioning
confidence: 99%
“…Stimulation of the immune system can also be achieved by synthetic molecules, such as mifamurtide (immune modulator liposomal muramyl tripeptide), which is a synthetic derivative of a peptidoglycan that makes up the plasma membrane of bacillus Calmette–Guerin. In cancer, mifamurtide induces the activation of monocytes and macrophages against tumors via the secretion of IL-6, TNFα and increased anti-tumor activity of infiltrating immune cells [ 166 ]. The addition of mifamurtide showed an increase in event-free life span and overall survival [ 167 , 168 ] but without a significant difference between non metastatic and metastatic patients [ 169 ].…”
Section: New Therapeutic Approaches In Osmentioning
confidence: 99%
“…The most common malignant tumor that arises from the bone is osteosarcoma (OGS). This is commonly observed in children and the middle-aged population [1]. The histological investigations found that OGS typically arises from the mesenchymal stem cells and spindle cells that characterize osteoid formation [2].…”
Section: Introductionmentioning
confidence: 98%
“…The histological investigations found that OGS typically arises from the mesenchymal stem cells and spindle cells that characterize osteoid formation [2]. Therefore, curative approaches such as surgery and chemotherapy were employed as treatment options that typically showed unsatisfactory results in patients [1]. The commonly known chemotherapy drugs include Doxorubicin, Methotrexate, Cisplatin, and other combinational drugs that are often accompanied by significant side effects [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the high invasiveness and metastasis of OS is the fundamental reason for its aggressiveness, leading to a significant relapse rate. Patients with OS metastasis, particularly those with lung metastasis, have a five-year survival rate of less than 30% [ 8 , 9 , 10 ]. Consequently, focusing on the novel potent chemotherapy regimens is constantly a hot topic in the field of osteosarcoma therapy and plays a key role.…”
Section: Introductionmentioning
confidence: 99%